Women’s empowerment, agricultural extension, and digitalization: Disentangling information and role-model effects in rural Uganda - Lecoutere, Els; Spielman, David J.; Van Campenhout, Bjorn (International Food Policy Research Institute, 2020)
Women often have less access to agricultural information than men, constraining their participation in decision-making on crops, technologies, and practices. In the design of agricultural extension programs, women may be viewed as insignificant actors in agricultural production. Moreover, even if their role is recognized, valuable information on production does not flow freely within the household from men to women. Among groups of maize-farming households in eastern Uganda, we explore the impacts on women’s empowerment from the use of gender-responsive information and communication technologies to provide extension services, specifically videos that feature women as information providers. The research tests the relative impact of the videos, contrasting their informational effects versus their role model effects, on women’s knowledge, their agency, and their achievements in farming. The results show that targeting women with information increases their achievements in farming.